Strategies to Enhance Job Satisfaction through Organizational Justice, Work Environment, and Rewards at PT Nanda Putra (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The high level of job dissatisfaction reported by 41% of workers in Indonesia poses a serious challenge for companies, as it can potentially increase turnover and decrease productivity. This phenomenon underscores the importance for PT Nanda Putra, as a company operating in a competitive industry, to identify factors that enhance job satisfaction. This research aims to analyze the influence of organizational justice, work environment, and rewards on job satisfaction. This study utilized a quantitative approach with a causal-associative design and included 80 respondents chosen through simple random sampling. Primary data were gathered through a Likert-scale questionnaire and analysed using multiple linear regression with the aid of SPSS software. The results of the analysis show that organizational justice, work environment, and rewards collectively exert a significant positive effect on job satisfaction (p < 0.05). Based on these findings, it is recommended that the company strengthen procedural and informational justice, improve the safety and comfort of the work environment, and implement a fair and meaningful reward system as strategic measures to enhance job satisfaction.